SOME FINDINGS ON THE POLITICAL PARTICIPATION OF GENERATION Z YOUTH IN TÜRKİYE : Received: 28th November 2024 Revised: 7th December 2024, 10th December 2024 Accepted: 5th December 2024 - Akyol, Ender; Erarslan, Fatih (PEOPLE: International Journal of Social Sciences, 2024)
In recent years, there has been significant interest in generational studies across various disciplines of social sciences. Particularly, the political participation behaviors and voting tendencies of individuals known as Generation Z have drawn the attention of both academicians and political decision-makers. However, in Türkiye, studies examining the relationship between generational voter tendencies and political participation preferences are limited and are generally conducted on a regional or educational basis, focusing on specific provinces, regions, or schools. Based on the assumption that a descriptive and explanatory study on the general political participation tendencies of Generation Z in Türkiye is needed, this research was designed. The study considered citizens living in Türkiye as the population, and a representative sample was determined. Since the variable in question would be measured at the societal level, the sample was distributed at the NUTS II level. To achieve a representative sample, a minimum size of 417 was calculated with a ±3% margin of error at a 95% confidence level. Accounting for potential missing data, the sample size was increased to 500. The sample included 26 provinces and 31 districts from Level 2 of Türkiye's Statistical Regional Units Classification. The data obtained were analyzed using SPSS (Statistical Packages for the Social Sciences), focusing on the general voter tendencies of Generation Z. The analyses included reliability analysis, frequency analysis, chi-square tests, and difference tests. The findings revealed that 85.8% of participants were not members of any political party, and 67.4% did not believe in solving problems through politics. Furthermore, 41.6% identified themselves as sympathetic voters, while 34.2% considered party leadership important in voting decisions. Additionally, 66.2% of respondents stated that Türkiye needs a new political party, and 60.6% expressed support for a return to the parliamentary system.